(untitled) (ResearchJet Journal of Analysis and Inventions, 2023)
This article delves into the fascinating realm of childhood writings and examines the prominent role of fantasy in shaping young minds. It explores how the use of fantasy elements in children’s literature and storytelling nurtures imagination and creativity, fostering cognitive and emotional development.